دور المعرفة التسويقية في إختيار المشاريع-دراسة حالة مؤسسة إتصالات الجزائر بالأغواط - نقموش إبتهال فاطمة الزهراء; سعود حكيمة; خنيش يوسف (جامعة عمار ثليجي الاغواط, 2022)
This research study aims to identify the role of marketing knowledge as an important parts of knowledge management and how its application is reflected in the selection of projects, given the various modern approaches in this field, where the study focused on ALGERIA TELECOM as a community for the study and on a number of employees in the institution as a sample, the questionnaire was used as a statistical tool for collecting and analyzing information based on the statistical tools of the SPSS and SMARTPLS programs. It was concluded that marketing knowledge directly contributes to the selection of projects by relying on the correct methods for collecting this marketing information. The study also reached a set of suggestions, the most important of which is that every economic institution should work to enhance and apply marketing knowledge in various project selection processes.